The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/rda.13379
|View full text |Cite
|
Sign up to set email alerts
|

Influence of idebenone on ram semen quality stored at 4°C

Abstract: Contents The current study was designed to investigate the effect of idebenone (Id), an antioxidant on ram semen quality. Semen samples were collected, pooled and diluted in a Tris‐based extender supplemented with 0, 1, 2, 4 and 8 µM idebenone. Computer‐assisted sperm analysis was used to evaluate spermatozoa kinematics. Sperm viability and membrane functionality were assessed respectively, by eosin‐nigrosin staining and HOS test. Biochemical assays were carried out to measure different metabolites in spermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Scavenging potential of IDB against toxicity of different reactive oxygen species was shown previously (Mordente et al, 1998). Studies which conducted on ram revealed that IDB treated groups (at proper concentration) had lesser hydroperoxide and malondialdehyde values compared to control sample upon liquid storage or after freezing/thawing process of semen (Eslami et al, 2019;Lone et al, 2019). Probable protective role of IDB may due to attenuation of oxidative and peroxidative toxicity induced by DEL during low temperature liquid semen storage.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Scavenging potential of IDB against toxicity of different reactive oxygen species was shown previously (Mordente et al, 1998). Studies which conducted on ram revealed that IDB treated groups (at proper concentration) had lesser hydroperoxide and malondialdehyde values compared to control sample upon liquid storage or after freezing/thawing process of semen (Eslami et al, 2019;Lone et al, 2019). Probable protective role of IDB may due to attenuation of oxidative and peroxidative toxicity induced by DEL during low temperature liquid semen storage.…”
Section: Discussionmentioning
confidence: 79%
“…It was reported that cooling of spermatozoa induces irreversible damages, and change the spermatozoa function and fertilization potential (Evans and Maxwell, 1987). Then, addition of protective substances to semen extender have been examined by different studies, to ameliorate oxidative toxicity upon preservation (Câmara et al, 2011;Akalin et al, 2016;Eslami et al, 2019). Current study indicated greater amounts of MDA in DEL exposed group compared to combination groups.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A synthetic analogue of coenzyme Q10, idebenone (2-(10-hydroxydecyl)-5,6dimethoxy-3-methyl-cyclohexa-2,5-diene-1,4-dione) has been reported as a potent antioxidant [113]. Idebenone has been shown to be an efficient antioxidant additive during 72 h storage at 4˚C, improving cell membrane functionality and viability by ameliorating nitrosative and peroxidative stress [114].…”
Section: Other Compoundsmentioning
confidence: 99%